PERANCANGAN WEBSITE MULTIMEDIA MENGGUNAKAN METODE WATERFALL UNTUK MEMASARKAN BISNIS SEWA ALAT CAMP - Alif Shahputra Hutasoit; Supiyandi; Ricky Ramadhan harahap (CV. Hawari, 2026)
The development of information technology has encouraged business actors to utilize digital media as a more effective and efficient means of promotion. CMD OUTDOOR is a camping equipment rental service business that still uses conventional promotional media so that the range of information to the public is limited. This research aims to design and build a multimedia website as a promotional and information medium for CMD OUTDOOR using the Waterfall method. The development methods applied include the stages of needs analysis, system design, implementation, testing, deployment, and maintenance. The website is developed using HTML, CSS, and JavaScript technology and is equipped with multimedia elements in the form of text, images, and visual information that supports the delivery of information to users. The results of the study show that the website built is able to display business profile information, rental product lists, galleries, and contact information in a structured and easily accessible manner. Based on the test results, all website features can run well according to the needs that have been determined. The presence of this website is expected to increase the effectiveness of promotions, expand marketing reach, and strengthen the professional image of CMD OUTDOOR in the digital era.